2011
DOI: 10.1074/jbc.m110.191098
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Structural Insights into the Regioselectivity of an Acyl-CoA Fatty Acid Desaturase via Directed Molecular Evolution

Abstract: Membrane-bound fatty acid desaturases and related enzymes play a pivotal role in the biosynthesis of unsaturated and various unusual fatty acids. Structural insights into the remarkable catalytic diversity and wide range of substrate specificities of this class of enzymes remain limited due to the lack of a crystal structure. To investigate the structural basis of the double bond positioning (regioselectivity) of the desaturation reaction in more detail, we relied on a combination of directed evolution in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…Rat hepatocytes were incubated for 24 h with media supplemented with TVA or [1][2][3][4][5][6][7][8][9][10][11][12][13] C]TVA and with a control medium without FA. RA (R t = 27.5 min) produced by ⌬ 9-desaturation of TVA was easily detected (7.6 ± 3.2% of FA, n = 5) in the cells incubated with TVA or 13 C-TVA ( Fig.…”
Section: Biosynthesis Of the Suspected Trans 11 Cis 13-cla In Rat Hementioning
confidence: 99%
See 1 more Smart Citation
“…Rat hepatocytes were incubated for 24 h with media supplemented with TVA or [1][2][3][4][5][6][7][8][9][10][11][12][13] C]TVA and with a control medium without FA. RA (R t = 27.5 min) produced by ⌬ 9-desaturation of TVA was easily detected (7.6 ± 3.2% of FA, n = 5) in the cells incubated with TVA or 13 C-TVA ( Fig.…”
Section: Biosynthesis Of the Suspected Trans 11 Cis 13-cla In Rat Hementioning
confidence: 99%
“…The pure trans 11, trans 13-18:2 was obtained from Larodan (Malmö, Sweden). [1][2][3][4][5][6][7][8][9][10][11][12][13] C] trans -vaccenic acid (chemical purity 95%, isotopic enrichment 99%) was synthesized by the Commissariat à l'Energie Atomique (CEA, Gif-sur-Yvette, France) according to well-established procedures ( 27,28 ). FA albuminic complexes were prepared as described ( 26 ).…”
Section: Incubation Of Cells With Fatty Acidsmentioning
confidence: 99%
“…The mFADs and their mutants are typically functionally characterized in the yeast S. cerevisiae [151] or in baculovirus-insect cell expression systems [79]. These experiments led to the identification of sequence determinants of both acyl-CoA and acyl-lipid mFAD specificities in diverse organisms, such as transmembrane helices or conserved histidine-rich motifs [55,59,[152][153][154][155][156][157][158][159][160][161][162]. Buček et al [82] identified a critical amino acid residue in the transmembrane domain of an mFAD from Manduca sexta (MsexD3) that determines the specificity and ability of this desaturase to catalyze biosynthesis of FAs containing three conjugated double bonds via E/Z14 desaturation from diunsaturated FAs.…”
Section: Structural Determinants Of Mfad Functionmentioning
confidence: 99%
“…Site-directed mutagenesis based on amino acid sequence comparison has been used to identify amino acids participating in the substrate specifi city of Mucor rouxii D6d ( 15 ), Siganus canaliculatus ⌬ 4 and D5d/D6d ( 16 ), and marine copepod ⌬ 9 desaturase ( 17 ). The regioselectivity of house cricket ⌬ 12/ ⌬ 9 desaturase was investigated using chemical mutagenesis and yeast complementation assays ( 18 ). Moreover, fatty acid-modifying enzymes with protein structures similar to, but chemoselectivities different from, the fatty acid desaturases have been used to swap the function of Arabidopsis oleate 12-desaturase and hydroxylase ( 19 ) and to alter the product partitioning between Crepis alpina ⌬ 12 desaturase and acetylenase ( 20 ) and Momordica conjugase itself ( 21 ).…”
Section: Site-directed Mutagenesismentioning
confidence: 99%